Celestial Cities: The Poetics of Supernal Space in Italian Literature from Luzzatto to Calvino - Goodman, Daniel Ross (Quaderni d'Italianistica)

(untitled) (Iter Press, 2025)
This article examines the supernal city motif in Italian literature as an imaginative response to earthly territorial conflicts, spanning Dante Alighieri’s Divina Commedia (early 14th century), Moses Chaim Luzzatto’s kabbalistic Mishkenei Elyon (18th century), and Italo Calvino’s Le città invisibili (1972). Rooted in Augustine’s City of God and biblical precedents, Dante innovates a theatrical, eternal heavenly Jerusalem superior to its terrestrial twin, employing “accommodated speech” to convey the ineffable. Luzzatto inverts Jewish theology by deriving earthly holiness from a celestial Temple, prioritizing mystical sanctity amid Enlightenment disputes. Calvino secularizes the trope with sublime, psychological cities that evade utopian clarity. Despite medieval Christian, Jewish mystical, and postmodern secular divides, these works unite around the common theme of redirecting focus from contested lands to the realm of the boundless imagination, thereby offering us a compelling model for non-violent worldview reconciliation. Invoking Frye’s anatomy, Bakhtin’s chronotope, Deleuze, and Lefebvre, this article posits Italian literature’s celestial cities as constructs that de-amplify jingoism, channeling energies from earth-bound conflict toward supernal peace-building and cooperation.